FORMS OF EXISTENCE OF THE UNIVERSE IN FAKHR AL-DIN AL-RAZI - Sokhibjon Umarjonov (American Journals Publishing, 2024)
The study examines Fakhr al-Din al-Razi’s attitude to the principles of physics and categories such as atom, void, place, time, motion and quiescence, which are the forms of existence of the universe. During the research, the works written by Fakhr al-Din al-Razi and the scientific exploration of Western and local orientalists dedicated to the study of the thinker’s life, scientific heritage, religious-philosophical, and metaphysical outlook were used as crucial sources. In recent years, Fakhr al-Din al-Razi’s personality, scientific heritage, philosophical and religious outlook have been widely studied by Western scientists and are the cause of their great interest. In this regard, during our research, the principles of interrelatedness and systematicity; an attempt was made to solve the problems posed by the topic using research methods such as comparative-historical, hermeneutic, comparative analysis, and scientific objectivity.
Keywords: Atom, atomic substance, jawhar atomism, forms of existence, kalam tradition, “Platonic” understanding, continuism, eternity, void, body, place, time, motion, quiescence.